Immobilization and characterization of hormone-sensitive lipase (HSL) from Glaciozyma antarctica - Ishak, Siti Nor Hasmah; Rahman, Raja Noor Zaliha Raja Abd.; Kamarudin, Nor Hafizah Ahmad; Leow, Adam Thean Chor; Ali, Mohd Shukuri Mohamad (Elsevier BV, 2024)
HSL-like esterase (GlaEst12) was isolated from the psychrophilic yeast Glaciozyma antarctica, and has a broad substrate specificity hence allowing hydrolysis of a wide range of ester molecules. This characteristic makes it relevant in a variety of industries, including food processing, pharmaceutical, and bioenergy. Immobilization of HSL-like esterase from G. antarctica (GlaEst12) was achieved through physical adsorption onto different types of supports such as Amicogen LKZ118, Amicogen LKZ518, Accurel MP1000, Seplite LXC621, and Seplite LX120. Among these, LKZ518 and LX120 exhibited a high immobilization rate (95 - 100 %), surpassing the other tested supports. Nonetheless, their recorded enzyme activity was notably lower when contrasted with the activity observed on LKZ118. While LKZ118 displayed a 50 % immobilization rate, it demonstrated remarkably high enzyme activity compared to the other supports. The optimal enzyme concentration for immobilization was determined to be 5 mg per gram of LKZ118 support. The immobilized lipase (GlaEst12_LKZ118) showed an optimum temperature et 60 °C similar to free GlaEst12 when tested using pNP-octanoate substrate. However, it showed a shift in pH optimum from pH 8 for free GlaEst12 to pH 9 for GlaEst12_LKZ118. GlaEst12_LKZ118 demonstrated prolonged stability at 60 °C, with a half-life of 180 min. Furthermore, it exhibited stability in the presence of methanol when treated at 50 °C, and increased activity in the presence of DMSO. Operational stability tests revealed that GlaEst12_LKZ118 maintained 65.5 % of its relative activity after 7 cycles, indicating its robust operational stability. In summary, the study demonstrated the successful immobilization of HSL lipase derived from G. antarctica using various supports and the immobilized enzyme showed promising activity levels for potential applications in biodiesel production and flavour ester synthesis.